Investigation of thermoelectric characteristics of MoS₂ in bulk and thin film structures - Muntini, Melania Suweni; Rahayu, Irasani; Insawang, Mekhala; Dewayanti P, Widya; Ruamruk, Surasak; Thaowankaew, Somporn; Fatimah, Iim; Seetawan, Tosawat; Voraud, Athorn (Creative Science, 2026)
In this work, we investigated and compared the thermoelectric properties of molybdenum disulfide (MoS2) in bulk and thin-film structures. The bulk MoS2 was synthesized by hot pressing (HP) at 700°C from MoS2 nano-powder. While MoS2 thin film was fabricated via radio-frequency (RF) magnetron sputtering at ambient temperature using a MoS2 bulk target and then annealed at 700oC. After bulk and thin-film MoS2 samples were prepared, the characterization of crystal structure, surface morphology, and atomic composition was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX), respectively. The electrical resistivity (ρ) and Seebeck coefficient (S) were measured by the ZEM-3 method to determine the thermoelectric power factor (PF). The results revealed that bulk MoS2 exhibited p-type thermoelectricity. In contrast, the MoS2 thin films exhibited n-type thermoelectricity. Among the thermoelectric power factors, the highest power factor of bulk MoS2 was 0.52 mW m⁻¹ K⁻², while the highest power factor of thin film MoS2 was 3.14 mW m⁻¹ K⁻² at the temperature measurement 473K. GRAPHICAL ABSTRACT HIGHLIGHTS • The microstructure of MoS₂ has differed due to three-dimensional (bulk) and two-dimensional (thin film) to show the hexagonal phase for bulk and 2H for thin film. • The microstructure of MoS₂ has induced a p-type thermoelectricity on bulk structure and transferred to an n-type thermoelectricity on thin film structure. • The power factor of MoS₂ thin films was higher than that of bulk MoS₂, indicating superior electrical energy conversion efficiency in the thin-film structure.